Are all mismatch repair deficient endometrial cancers created equal? A large, retrospective, tertiary center experience - Capasso, Ilaria; Perrone, Emanuele; Duranti, Simona; Giannarelli, Diana; Nero, Camilla; Cordisco, Emanuela Lucci; Pomponi, Maria Grazia; Remondini, Laura; Piermattei, Alessia; Valente, Michele; Santoro, Angela; Esposito, Giovanni; et al. (European journal of cancer (1990), 2025)
One third of endometrial carcinomas (ECs) presents with mismatch repair deficiency (MMRd). Of these, 70 % are caused by somatic hypermethylation of MLH1 promoter; the remaining cases are determined by Lynch syndrome or double somatic inactivation of MMR genes. Although associated with good-intermediate prognosis, heterogeneity in treatment response and survival has been reported among MMRd ECs. We aim to investigate differences in pathologic aggressiveness and event-free survival (EFS) among three MMRd EC subtypes, classified by immunohistochemistry (IHC) and MLH1 methylation analysis. Subjects undergone surgical staging for EC were retrospectively included. IHC analysis was performed in all patients to assess MMR and p53 status. Methylation analysis was performed in MMRd patients with IHC-negative MLH1. The MMRd population was classified into: 1)MLH1-hypermethylated (MLH1-HyMet); 2)MLH1-unmethylated (MLH1-UnMet); 3)IHC-negative MSH2 and/or MSH6 or PMS2 alone (non-MLH1). Of 1171 patients undergoing surgical staging and IHC assessment, 362 (30.9 %) were classified as MMRd and included in the analysis. Among these, 59.7 % (n = 216) were MLH1-HyMet, 11 % (n = 40) MLH1-UnMet, and 29.3 % (n = 106) non-MLH1. Compared to MLH1-UnMet and non-MLH1, MLH1-HyMet was associated with older age, higher BMI, larger tumor size, deeper myometrial invasion, substantial lymphovascular space invasion, lower frequency of early-stage and low-risk disease. EFS was similar when comparing the MMRd subtypes, even after adjusting for stage and tumor histology. However, a trend of MLH1-HyMet toward poorer prognosis can be observed, particularly in the advanced/metastatic setting. MLH1-hypermethylated MMRd ECs display more aggressive clinicopathologic features compared to the other MMRd subgroups. However, although a suggestive trend toward poorer EFS was observed in the hypermethylated subset, particularly in the advanced setting, no significant differences in prognosis were detected among the MMRd subtypes. •Potential differences among MMRd subtypes have been underexplored in EC.•MLH1-hypermethylated ECs display more aggressive features compared to unmethylated MMRd.•No significant prognostic differences among MMRd subtypes were detected.•However, trends towards poorer prognosis of MLH1-hypermethylated tumors were observed.